Breakdown of the Anglo-Saxon Model of Globalization - Izvekov, Arkady I. (Journal of History Culture and Art Research, 2018)
The most advanced societies have no newly-needed democratic formations, as legally unsecured intellectual freedom may be usurped by powerful institutions having a formal respect for the old democratic principles. Generally, this means that we are witnessing not just personality changes, but tectonic shifts in the legal and political strata that existed and developed within the period of Modernity. The purpose of this research is to identify the features of current crisis in the Anglo-Saxon globalization. This goal can be achieved on the back of classical philosophy and large-scale historical material applied simultaneously. This approach demonstrates that globalization processes are still guided by the legacy of early English history and the ideas that originated during the Age of Enlightenment. Anglo-Saxon Model discredits itself and, consequently, becomes non-legitimate when it comes to its supreme right to interpret the idea of democracy. An important aspect of this research is how the religious trends of the 17th century were interwoven with political, legal and cultural consequences.